Evaluation The role of Trefoil Factor1 as early stage biomarker in patients with Nephrolithiasis - “Mohammed Abdullah Ajeel; Zaid Mohammed Mubarak Al-Mahdawi (Tikrit Journal of Pure Science, 2023)
Nephrolithiasis is a public health problem that affect large scale of peoples around the world. naturally, there are many substances ,proteins, lipids, glycosaminoglycans and inorganic compounds, work as kidney stone inhibitors in the normal renal tubular fluid that inhibit crystal growth, aggregation, and/or adhesion to renal surfaces, among this inhibitors we investigate the concentration of trefoil factor 1 (TFF1) as a stone formation inhibitor and kidney injury biomarker in serum of 75 kidney stone patients and 15 healthy subjects using ELISA technique. The results shows no significant changes within patients groups while shows that TFF1 levels were significantly increased in stone patients when compared with the healthy controls (P≤0.05), which support the fact that it could use as early marker of kidney injury (KI) .The results also revealed no significant changes within patients groups while there was a significant changes between patients and controls for both blood urea and serum creatinine levels in renal stone patients in comparison to the apparently healthy control subjects (P ≤0.05). Further investigation are needed to show the inhibitory effect of TFF1 in urine of kidney stone patients.